Character Studies in the Fourth Gospel Narrative Approaches to Seventy Figures in John - Zimmermann, Ruben; Tolmie, D. Francois; Hunt, Steven A. (Mohr Siebeck, 2013)
Charakterstudien im vierten Evangelium. Eine narrative Annäherung an siebzig Figuren im Johannesevangelium.
PublicationDate: 20131113
Keywords: New Testament -- Literary Criticism -- Philosophische Theologie -- Neues Testament -- Array